DAMPAK KRIMINALISASI GURU TERHADAP MOTIVASI DAN KINERJA DI SEKOLAH DASAR - Khana, Febty Aviya; Madjdi, Ahmad Hilal; Hariyadi, Ahmad (Equity In Education Journal, 2025)
This study aims to describe the impact of criminalization on teacher motivation and performance in several public elementary schools in Geyer District, Grobogan Regency, Central Java Province. Using a qualitative approach, data were collected through in-depth interviews and observations of teachers and school principals. Data analysis used the interactive model from Miles et al. (2014), which includes data condensation, data presentation, and drawing conclusions. Data validation was conducted using source triangulation and member checking techniques. The results of the study indicate that the threat of criminalization triggers anxiety and lowers teachers' self-confidence, which results in decreased creativity and innovation in learning. Teachers tend to choose conventional methods to avoid legal risks, making interactions with students rigid and less meaningful. This tension also affects classroom dynamics and the learning atmosphere. The lack of institutional support and the absence of clear protection policies exacerbate teachers' psychological stress, ultimately negatively impacting their motivation and performance. This study recommends the need for a more empathetic institutional approach and adequate legal protection policies to create a safe working environment that optimally supports teachers' professionalism.